2020
DOI: 10.3390/su12156003
|View full text |Cite
|
Sign up to set email alerts
|

Life Cycle Assessment of Thai Hom Mali Rice to Support the Policy Decision on Organic Farming Area Expansion

Abstract: Thailand has a strategic national policy to increase organic rice farming. This study firstly applied Life Cycle Assessment for evaluating the quantitative environmental impacts at the regional and national levels to facilitate the national policy decision on the expansion of organic rice cultivation areas. The impact categories of interest included global warming, terrestrial acidification, freshwater eutrophication, terrestrial ecotoxicity, and freshwater ecotoxicity, and the life cycle impact assessment met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Yodkhum et al [95] calculated the CF of conventional rice farming in the Maerim District, Chiang Mai province, Northern Thailand, and found 0.64 kg CO2eq kg −1 rice yield. Mungkung et al [96] found that the CF of Hom Mali organic rice production in the Surin province, Northeast Thailand was 2.88 kg CO2eq kg −1 rice yield. When comparing the present study with the above studies, the different CF values are mainly due to the different amounts of agricultural inputs, methods, and parameters for the life cycle assessment (LCA) calculation, and none of the above studies considered SOC stocks.…”
Section: Greenhouse Gas Emissions and Carbon Footprint Of Of And Cvfmentioning
confidence: 99%
“…Yodkhum et al [95] calculated the CF of conventional rice farming in the Maerim District, Chiang Mai province, Northern Thailand, and found 0.64 kg CO2eq kg −1 rice yield. Mungkung et al [96] found that the CF of Hom Mali organic rice production in the Surin province, Northeast Thailand was 2.88 kg CO2eq kg −1 rice yield. When comparing the present study with the above studies, the different CF values are mainly due to the different amounts of agricultural inputs, methods, and parameters for the life cycle assessment (LCA) calculation, and none of the above studies considered SOC stocks.…”
Section: Greenhouse Gas Emissions and Carbon Footprint Of Of And Cvfmentioning
confidence: 99%
“…Of the organic LCA studies only two papers 37,38 and of comparative studies only six papers [39][40][41][42][43][44] included SOC in their assessment. Some other studies considered emissions from dLUC [45][46][47][48][49][50][51][52] .…”
Section: Methodological Choicesmentioning
confidence: 99%
“…For this reason, few studies on biodiversity impacts of agricultural production systems were available (Table 4). Of the four LCA studies that included BI of food products, two studies 47,52 focused on organic milk and rice production systems, respectively, and the two others reported on both organic and conventional milk production systems (Tables 2, 4).…”
Section: Functional Unit Based On Tablementioning
confidence: 99%
“…According to the Sustainable Development Goals (SDG), by 2030, the global agricultural system is supposed to make sustainable food production accessible to all people (Arunrat et al, 2021). Organic rice cultivation is encouraged owing to it is expected to lower risks from eliminating chemical inputs and reduce environmental impacts, including ecosystem degradation and global warming (Mungkung et al, 2020). It has been reported that the demand for organic rice in the international market is increasing and supposed to continue growing (Declaro-Ruedas, 2019).…”
Section: Driving Force Analysis Of the Formation Of Organic Rice Prod...mentioning
confidence: 99%